Cultivation of endogenous algal consortia for aquaculture wastewater remediation as a strategy toward net-zero carbon emission: from laboratory research to practical application - Yang, Limin; Lu, Qian (Frontiers in Nutrition, 2025)
IntroductionEndogenous algal consortia were cultivated in a recirculating aquaculture system to recover nutrients from wastewater and facilitate carbon sequestration.MethodsThis study investigated the microbial community composition of the algal consortia, the roles of algae and associated microorganisms, the optimization of operational parameters, and the carbon emissions of the pilot-scale system.Results and discussionThe results showed that filamentous algae, particularly Schizomeris sp., are the dominant species in algal consortia. The interaction of algae and bacteria enhanced biomass production (0.90 g/L) and improved TOC removal efficiency (80.38%), demonstrating the excellent performance of algal consortia in wastewater treatment. In laboratory research, under optimal conditions, the carbon retention of algae-based aquaculture wastewater treatment reached 185.20 mg carbon/L of wastewater. In the 150-day pilot-scale experiment, 50.76 kg of carbon (feed) was input into the aquaculture system, while 11.50 kg of carbon was outputted as fish product, and algae biomass containing 39.27 kg of carbon was produced, resulting in an aquaculture process with net-zero carbon emission. The results of this study will provide a theoretical basis and practical strategies for the development of an eco-friendly aquaculture mode toward carbon neutrality.